The Church: Towards a Common Vision - Александр ГЕЙЧЕНКО (Богословські роздуми: Східноєвропейський журнал богословʼя)
THE CHURCH: Towards a Common Vision. Faith and Order Paper No. 214, Geneva, World Council of Churches (WCC), 2013. - URL: http:// www.oikoumene.org/en/resources/documents/wcc+commissions/faith+and+order+commission/ i+unity+the+church+and+its+mission/the+church+towards+a+common+vision